GAGE is a method for identification of plant species based on whole genome analysis and genome editing - Hao, Lijun; Xu, Wenjie; Qi, Guihong; Xin, Tianyi; Xu, Zhichao; Lei, Hetian; Song, Jingyuan (Communications biology, 2022)
Whole genomes of plants should be ideal databases for their species identification, but unfortunately there was no such method before this exploration. Here we report a plant species identification method based on the whole Genome Analysis and Genome Editing (GAGE). GAGE searches for target sequences from the whole genome of the subject plant and specifically detects them by employing a CRISPR/Cas12a system. Similar to how Mendel chose Pisum sativum (pea), we selected Crocus sativus (saffron) to establish GAGE, in which we constructed a library containing all candidate target sequences. Taking a target sequence in the ITS2 region as an example, we confirmed the feasibility, specificity, and sensitivity of GAGE. Consequently, we succeeded in not only using GAGE to identify Cr. sativus and its adulterants, but also executing GAGE in the plants from different classes including angiosperms, gymnosperms, ferns, and lycophytes. This sensitive and rapid method is the first plant species identification method based on the whole genome and provides new insights into the application of the whole genome in species identification. A plant species identification method, GAGE, is reported that searches for target sequences from the whole genome of the subject plant and specifically detects them by employing a CRISPR/Cas12a system.